Analisis Perjanjian Pertahanan dan Keamanan Indonesia-Singapura - Simbolon, Khairunnisa (LP3M Universitas Dharma Wacana, 2025)
This study analyzes the dynamics of bilateral defense relations between Indonesia and Singapore through the Defense Cooperation Agreement (DCA) signed in 2007. Using a constructivist approach, this study explores how the construction of national identity and norms of sovereignty influence the two countries' perceptions of the DCA. Indonesia, as a large country with an anti-colonial tradition, tends to be sensitive to issues of sovereignty, while Singapore, as a vulnerable city-state, views this cooperation as an existential necessity. This research reveals an imbalance of benefits in the implementation of the DCA, with Singapore considered to be more advantaged, particularly in the use of military training areas in Indonesia. The analysis also shows that differences in perceptions and strategic priorities are the main obstacles to the ratification of the agreement. These findings reinforce the importance of ideational factors in understanding international relations, alongside material and rational considerations